Early-Age Tensile Strength of Concrete Containing Lowcalcium Fly Ash as Partial Replacement of Cement - Sarker, Prabir; Shrestha, Subin (Precast/Prestressed Concrete Institute, 2011)
The benefits of using fly ash include improvements of the durability and sustainability features of concrete. However, the slow strength development of low-calcium fly ash concrete at the early ages is viewed as a drawback in applications such as tilt-up, precast and prestressed concrete structures, where specified early-age strength is required. This study investigated the development of the early-age tensile strength of concrete containing locally available low-calcium fly ash. Fifteen concrete mixtures containing fly ash from 0 to 40% of the binder were designed. The 3-day compressive strength varied from 22 to 51 MPa (3 to7.4 ksi). The splitting tensile strengths at 3 and 28 days were calculated from the compressive strengths using the AS3600, ACI 318 and the EC2 Codes. The test-prediction ratios of splitting tensile strengths show that the early-age tensile strength correlated well with the compressive strengths. No effect of the early age or inclusion of fly ash was observed on the test-prediction ratios. This suggests that the Code equations based on the compressive strength can be used for designs related to early-age tensile strength of concrete containing up to 40% of low-calcium fly ash.